When we collide: sex, social risk, and Jewish ethics - Epstein-Levi, Rebecca (New Jewish philosophy and thought, 2023)
Part I: Groundings. 1. Textual intercourse: grounding sexual ethics in Jewish sources -- 2. Social intercourse: why sex Is enmeshed in sociality -- 3. Risky business: why risk is inherent in sociality -- Part II: Case studies on community and risk. 4. STIs: Infection, impurity, and managing social contagion -- 5. BDSM: Risk, pleasure, and polymorphous community.